(untitled) (Ushuluddin International Conference (USICON), 2017)
The development of internet and social media technology are a new phenomenon of contemporary Muslim lifestyle. The development of the era is used by certain groups in spreading their understandings. The medium used in mediating popular culture is the internet media, like Facebook, Instagram, and other applications. The groups of Cyber ??Community-FPI groups, cyber-army Muslims- as the object of the researcher’s study are result of the hermeneutical reception on religion in the form of a meme visualization. The presence of popular culture presents make researcher to review about how the phenomena of societies have performed reception to the understanding of religion (al-Qur